Status Hara Serapan Nitrogen Pada Kelapa Sawit Tanaman Menghasilkan (Studi Kasus di Kebun Rakyat Desa Perlabian Kecamatan Kampung Rakyat Kabupaten Labuhanbatu Selatan) - Frastio Ramadani; Hilwa Walida; Badrul Ainy Dalimunthe (JURNAL MAHASISWA AGROTEKNOLOGI (JMATEK), 2023)
South Labuhanbatu is a district in North Sumatra which is synonymous with a very large area of oil palm plantations. The area of oil palm plantations in South Labuhanbatu district is around 57,307 hectares with a total production of 640,196.60 tons. This study aims to determine the levels of nutrients uptake of nitrogen (N) in oil palm plants produce. So far, the status of testing for potassium nutrient uptake in people's plantations in Perlabian Village, Kampung Rakyat South Labuhanbatu District, has never been carried out. Fertilization and care are carried out through knowledge from generation to generation, so it is important to study the status of nitrogen uptake in oil palm leaves. This research was carried out using a semi-detailed free-level grid survey method with a density of 100 meters. A total of 6 leaf samples were taken on the 17th leaf midrib and then 70% alcohol was applied and put into a plastic sample for further testing in the laboratory of PT. Socfindo. The results showed that the 2nd leaf sample was deficient and 1, 3, 4, 5 and 6 leaf samples were at the optimum point. The uptake of N (nitrogen) in the leaves of oil palm plants in smallholder plantations in Perlabian Village, Kampung Rakyat District, showed that the total N content of leaves was included in the optimal category.Keywords: Nitrogen, Nutrient Uptake, Oil Palm Plants have